Implikasi Hukum Putusan Mahkamah Konstitusi Terhadap Perlindungan Hak Perempuan dan Anak - Moch. Muhibbin (Program Studi Hukum Keluarga Islam, 2022)
The human perspective on marriage has become increasingly critical, especially in relation to equal rights between men and women. Several times Law Number 1 of 1974 concerning Marriage, was submitted to a judicial review to the Constitutional Court. There were 3 (three) Constitutional Court decisions that granted the applicant, namely the Constitutional Court Decision Number 46/PUU-VIII/2010 relating to the position of children outside of marriage, the Constitutional Court Decision Number 69/PUU-XIII/2015 relating to marriage agreements, and the Constitutional Court Decision Number 22 /PUU-XV/2017 relating to the age limit for marriage. The author examines the juridical aspect of the influence of 2 (two) Constitutional Court decisions, Decisions Number 46/PUU-VIII/2010 and Number 22/PUU-XV/2017 on elements of discrimination and violations of the protection of the basic rights of women and children. This study uses a normative legal research methodology through a qualitative descriptive approach. The results of the study concluded that the two decisions legally have implications for the elimination of elements of discrimination and violations of the protection of the basic rights of women and childrenCara pandang manusia terhadap perkawinan telah semakin kritis, terutama terkait dengan persamaan hak antara laki–laki dan perempuan. Beberapa kali Undang-undang Nomor 1 Tahun 1974 tentang Perkawinan, diajukan uji materi (judicial review) ke Mahkamah Konstitusi. Terdapat 3 (tiga) putusan MK yang mengabulkan pemohon, yaitu Putusan MK Nomor 46/PUU-VIII/2010 yang berkaitan dengan kedudukan anak di luar nikah, Putusan MK Nomor 69/PUU-XIII/2015 yang berkaitan dengan perjanjian perkawinan, dan Putusan MK Nomor 22/PUU-XV/2017 yang berkaitan dengan batas usia perkawinan. Penulis mengkaji aspek yuridis pengaruh 2 (dua) putusan MK, Putusan Nomor 46/PUU-VIII/2010 dan Nomor 22/PUU-XV/2017 terhadap unsur diskriminasi dan pelanggaran perlindungan terhadap hak dasar perempuan dan anak. Penelitian ini menggunakan metodologi penelitian hukum normatif melalui pendekatan deskriptif kualitatif. Hasil penelitian menyimpulkan bahwa kedua putusan tersebut secara yuridis berimplikasi terhadap penghapusan unsur diskriminasi serta pelanggaran perlindungan terhadap hak dasar perempuan dan anak.